The state presence in the firm and the state presence in the export destination economy: a Colombian firm's analysis - Vega Salas, William Gonzalo (2025)
This research analyses the relationship between state presence within firms and state presence in export destination economies; and the moderating role of export diversification in the relationship between these two manifestations of state presence. It presents the hypothesis that these is a positive relationship between state presence within firms and state pres-ence in the export destination economy, and that export diversification has a negative moderating role. Despite the ongoing process of marketization, liberalization, and privatization in emerging economies, the presence of the state within a firm enhances the ability to export, especially to countries with a high state presence. However, when such a firm exports to several destinations, it reduces its export to countries with a high state presence. The study was based on institutional theory and data from Colombian firms, from 2009 to 2016.